2021
DOI: 10.1002/jhbp.1084
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic papillectomy for tumors of the minor duodenal papilla: A case series of six patients and literature review

Abstract: Background/Purpose Various tumors of the minor duodenal papilla have been reported, most of which are treated by laparotomy. Although early‐stage tumors of the major papilla are increasingly being treated by endoscopic resection with relative ease and low invasiveness, there are only a few reports on endoscopic resection of tumors in the minor papilla. Methods Six patients with tumors in the minor papilla were treated by endoscopic papillectomy (EP), and their clinical and histopathological data were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…9 Though endoscopic resection of the minor papilla neoplasia is seldom reported, case reports and small case series have suggested that EP is also an alternative treatment for minor papillary tumors. 10,18 The most common indication for EP is benign adenoma of the pancreatic duct or bile duct with no intraductal involvement. 19 Surgical resection is required for malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Though endoscopic resection of the minor papilla neoplasia is seldom reported, case reports and small case series have suggested that EP is also an alternative treatment for minor papillary tumors. 10,18 The most common indication for EP is benign adenoma of the pancreatic duct or bile duct with no intraductal involvement. 19 Surgical resection is required for malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, studies have revealed that EP is a safe and minimally invasive alternative to pancreatoduodenectomy for the treatment of ampullary adenoma 9 . Though endoscopic resection of the minor papilla neoplasia is seldom reported, case reports and small case series have suggested that EP is also an alternative treatment for minor papillary tumors 10,18 …”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic papillectomy (EP) is a safe and effective alternative to surgery for ampullary tumors, but several procedure‐related adverse events can occur 1–4 . In particular, management of papillary stenosis is technically challenging 5 .…”
Section: Figurementioning
confidence: 99%
“…Endoscopic papillectomy (EP) is a safe and effective alternative to surgery for ampullary tumors, but several procedure-related adverse events can occur. [1][2][3][4] In particular, management of papillary stenosis is technically challenging. 5 Here, we present a case of successful biliary cannulation using the endoscopic ultrasound-guided rendezvous (EUS-RV) technique for bile duct stenosis after EP.…”
mentioning
confidence: 99%
“…En el reporte de caso la anatomía patológica confirmó el diagnóstico de adenocarcinoma bien diferenciado de tipo intramucoso con displasia de alto grado epitelial, y la ecoendoscopia permitió delimitar la lesión a la mucosa y submucosa superficial. (8,21) La guía de la Sociedad Europea de Endoscopia Gastrointestinal (ESGE) recomienda la papilectomía endoscópica en pacientes con adenoma ampular sin extensión intraductal, debido a buenos resultados en cuanto a pronóstico (éxito técnico y clínico, morbilidad y recurrencia); y la colocación profiláctica de stent en el conducto pancreático para reducir el riesgo de pancreatitis posterior a la papilectomía endoscópica, además aconseja el seguimiento a largo plazo de los pacientes después de una papilectomía endoscópica o ampulectomía quirúrgica (22,23).…”
Section: Discussionunclassified